2013
DOI: 10.1523/jneurosci.4578-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

The nNOS-p38MAPK Pathway Is Mediated by NOS1AP during Neuronal Death

Abstract: Neuronal nitric oxide synthase (nNOS) and p38MAPK are strongly implicated in excitotoxicity, a mechanism common to many neurodegenerative conditions, but the intermediary mechanism is unclear. NOS1AP is encoded by a gene recently associated with sudden cardiac death, diabetes-associated complications, and schizophrenia (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(132 citation statements)
references
References 68 publications
6
121
0
5
Order By: Relevance
“…The activated ASK1 itself activates promitogen activated protein kinase kinase MEKK3/6, MKK4/7, and JNK by a phosphorylation cascade. The activated JNK promotes the release of cytochrome C and the formation of an apoptosome, thus leading to apoptosis (Li et al, 2013;Arshad et al, 2013). Moreover, dual-luciferase report and Western blot assays showed that miR-21 obviously reduced the expression of FASLG.…”
Section: Discussionmentioning
confidence: 99%
“…The activated ASK1 itself activates promitogen activated protein kinase kinase MEKK3/6, MKK4/7, and JNK by a phosphorylation cascade. The activated JNK promotes the release of cytochrome C and the formation of an apoptosome, thus leading to apoptosis (Li et al, 2013;Arshad et al, 2013). Moreover, dual-luciferase report and Western blot assays showed that miR-21 obviously reduced the expression of FASLG.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that recruitment of the Ca 2? -dependent enzyme nNOS via PSD95 is a key contributor to neuronal dysfunction [19][20][21][22][23][24]. Our result showed that interaction of APPL1 with PSD95 through the PDZ2 domain results in activation of the neuroprotective Akt pathway.…”
Section: Appl1 S707a Disrupts Synaptic Activity-mediated Activation Omentioning
confidence: 88%
“…It was reported that the nNOS-p38MAPK pathway is mediated by CAPON during neuronal death after an excitotoxic stimulus. 27 L-TAT-GESV, a cell-permeable peptide, can compete for the unique PdZ domain of nNOS that interacts with CAPON and can double the amount of survival tissue in a severe model of neonatal hypoxia-ischemia. CAPON may be a new high-specificity target for ischemia.…”
Section: Downstream Molecules Of Nnosmentioning
confidence: 99%
“…Cao et al 37 found that NOS inhibitors reduce both glutamate-induced p38 activation and the resulting neuronal death. Li et al 27 reported that excitotoxic activation of p38MAPK and subsequent neuronal death were reduced by competition with the nNOS-CAPON interaction and by knockdown with CAPON-targeting small interfering RNAs. nNOS-CAPON uncouplers and p38MAPK inhibitors may become new types of anti-ischemia drugs.…”
Section: Downstream Molecules Of Nnosmentioning
confidence: 99%